Proficiency masterclass : student's book - Gude, Kathy; Duckworth, Michael (Oxford : Oxford University Press, 1994)
In sickness and in health. First impressions. Safety and danger. Stranger than fiction. It broadens the mind. Art for art's sake? Only flesh and blood. Words speak volumes. The call of the Wild...
Keywords: English language; Foreign speakers; English language -- Study and teaching -- Textbooks for foreign speakers